The Effects of Heat Stress on Haematological Parameters in Production Department of Food Industry Employees - Kanbur, Savas; Sayin, Irmak (Journal of the Pakistan Medical Association, 2023)
Objective: Haematological to investigate the effects of heat stress on some haematological parameters among food industry employees working in the production department. Method: The ambispective, single-centre, case-control study was conducted from December 1, 2016, to June 6, 2018, at Istanbul Gedik University and the Okan University, Istanbul, which is part of the Marmara region of Turkey. The study comprised subjects of either gender aged 22-57 years. Those working in the food industry were the cases in group A, while healthy controls formed group B. Within group A, subjects who were office workers formed subgroup A1, while those in the production department working in the heat treatment areas exposed to high temperatures formed subgroup A2. Heat stress in the environment was evaluated using the Wet Bulb Globe Temperature index. Peripheral blood haemoglobin and platelet levels, neutrophil-lymphocyte ratio and platelet-lymphocyte ratio were compared between the cases and the controls. Data was analysed using SPSS 22. Results: Of the 257 subjects, 139(54.1%) were women and 118 45.9%) were men. The overall mean age was 35.07±7.32. There were 143(55.6%) subjects in group A and 114(44.4%) in group B. Within group A, 19(13.3%) subjects were in subgroup A1 and 124(86.7%) in subgroup A2. The mean working duration for group A was 9.95±4.37 years (range: 5-24 years with). Haemoglobin and platelet levels were significantly lower and the neutrophil-lymphocyte ratio was significantly higher in subgroup A2 compared to those in subgroup A1 and group B (p<0.05). There was no significant difference in terms of platelet-lymphocyte ratio (p=0.486). Conclusion: Differences in haematological parameters were significantly different in individuals who worked in the production department and were exposed to heat stress compared to those who did not. Key Words: Haematological parameters, Heat stress, Food industry, Production department, Occupational health.